2008
DOI: 10.1016/j.psyneuen.2007.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal stress does not alter innate novelty-seeking behavioral traits, but differentially affects individual differences in neuroendocrine stress responsivity

Abstract: SummaryExposure to stress during prenatal or early postnatal life can dramatically impact adult behavior and neuroendocrine function. We recently began to selectively breed Sprague-Dawley rats for high (high responder, HR) and low (low responder, LR) novelty-seeking behavior, a trait that predicts a variety of differences in emotional reactivity, including differences in neuroendocrine stress response, fearand anxiety-like behavior, aggression, and propensity to self-administer drugs of abuse. We evaluated gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
67
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(74 citation statements)
references
References 73 publications
(102 reference statements)
7
67
0
Order By: Relevance
“…In addition, rats exposed to neonatal ventral hippocampal lesion display an attenuated increase in plasma corticosterone levels as compared with sham-lesion controls after 20 min of footshock, and this response fails to adapt after 60 min of footshock (Chrapusta et al, 2003). Similarly, the offspring of dams exposed to chronic unpredictable stress during pregnancy display an exaggerated corticosterone response to an open field test (Clinton et al, 2008). Taken together, these data suggest that USV and HPA axis responses to stress are sensitive to various developmental disruptions and that HPA axis dysregulation could contribute to other abnormal phenotypes seen in animal models of psychiatric disease.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, rats exposed to neonatal ventral hippocampal lesion display an attenuated increase in plasma corticosterone levels as compared with sham-lesion controls after 20 min of footshock, and this response fails to adapt after 60 min of footshock (Chrapusta et al, 2003). Similarly, the offspring of dams exposed to chronic unpredictable stress during pregnancy display an exaggerated corticosterone response to an open field test (Clinton et al, 2008). Taken together, these data suggest that USV and HPA axis responses to stress are sensitive to various developmental disruptions and that HPA axis dysregulation could contribute to other abnormal phenotypes seen in animal models of psychiatric disease.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we found that rats genetically selected for a passive stresscoping style also displayed hyperinsulinemia when exposed to a high-fat diet, indicating that the way an individual copes with stress may further influence their risk for type 2 diabetes (11). Although PNS has been suggested to influence the stress-coping strategy of the offspring, the direction and amplitude of these changes seem highly dependent on the sex of the offspring and the type of stressor used (12)(13)(14)(15)(16)(17)(18). In the current study, we test the hypothesis that PNS and stress-coping style may interact in predicting susceptibility to adverse metabolic conditions.…”
mentioning
confidence: 94%
“…For example, bLR rats also exhibit greater anxiety- and depressive-like behaviors following stressful experiences (i.e., Calvo et al 2011; Stedenfeld et al 2011). Relative to bHRs, bLRs exhibit a higher physiological stress response (e.g., stress-induced defecation; Clinton et al 2014) and an attenuated corticosterone response to mild stressors, which appears to be a function of greater glucocorticoid receptor expression in the hippocampus (Clinton et al 2008), a finding also reported in outbred HR/LR rats (Kabbaj et al 2000). These bHR-bLR differences in HPA activity likely influence the dopamine system (e.g., RougĂ©-Pont et al 1998), which, in turn, could alter the response to cocaine (i.e., absence of bLR cocaine sensitization, GarcĂ­a-Fuster et al 2010) as well as stimulus-reward learning (Flagel et al 2010, 2011).…”
Section: Discussionmentioning
confidence: 80%
“…The hippocampus is one structure that has been implicated in the differences in “emotionality” between bHRs and bLRs (e.g., Clinton et al 2008). While the hippocampus is known to be particularly sensitive to stress (e.g., Gould and Tanapat 1999), and involved in several aspects of addiction liability (Castilla-Ortega et al 2016a), including drug-context memory (e.g., Meyers et al 2006) and relapse to drug-seeking (e.g., Vorel et al 2001), the current findings are the first to investigate the relationship between hippocampal cell genesis and Pavlovian conditioned approach responses, specifically as a consequence of adolescent cocaine exposure.…”
Section: Discussionmentioning
confidence: 99%